2001
DOI: 10.1034/j.1600-0528.2001.290204.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived oral health among three subgroups of Asian-Americans in New York City: a preliminary study

Abstract: Results suggest that there are ethnic differences in the perception of oral health status even after adjusting for clinical variables as well as for demographic variables in this particular group of Asian-American residents of New York City. Predictors associated with the perception of oral health are different for each ethnic group. When designing oral health promotion activities to diverse ethnic groups, the cultural characteristics of each subgroup should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…Although information on a special subgroup of young people such as patients or military personnel [13,14] is available, there are few studies targeting general young adults. Because factors associated with self-rated oral health differ by ethnicity [15], it is valuable to identify the determinants of self-rated oral health in Japanese young people.…”
Section: Introductionmentioning
confidence: 99%
“…Although information on a special subgroup of young people such as patients or military personnel [13,14] is available, there are few studies targeting general young adults. Because factors associated with self-rated oral health differ by ethnicity [15], it is valuable to identify the determinants of self-rated oral health in Japanese young people.…”
Section: Introductionmentioning
confidence: 99%
“…Essa percepção depende da compreensão do indivíduo do que é normal na saúde bucal e de sintomas específi-cos que ele apresenta 3 . Indicadores desenvolvidos para mensurar percepções subjetivas de saúde bucal incluem a autoavaliação da saúde bucal, a percepção da necessidade de tratamento, como também a satisfação com o estado de saúde bucal.…”
Section: Introductionunclassified
“…Factors as low educational level, unemployment, long period since the last dental appointment, treatment requirements, lost teeth, dry mouth, and difficulty in eating are related to the negative self-perception [6,8,[12][13][14]. Other studies found that the positive oral health self-perception is associated with low ages, high income, higher educational level, low DMFT index and small time elapsed since the last appointment [4,11].…”
Section: Introductionmentioning
confidence: 94%
“…The subjective vision enable the health managers to evaluate comprehensively the needs and allow the planning of actions for oral health care [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation